2000
DOI: 10.1016/s0896-6273(00)00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Number of Hypocretin Neurons in Human Narcolepsy

Abstract: Murine and canine narcolepsy can be caused by mutations of the hypocretin (Hcrt) (orexin) precursor or Hcrt receptor genes. In contrast to these animal models, most human narcolepsy is not familial, is discordant in identical twins, and has not been linked to mutations of the Hcrt system. Thus, the cause of human narcolepsy remains unknown. Here we show that human narcoleptics have an 85%-95% reduction in the number of Hcrt neurons. Melanin-concentrating hormone (MCH) neurons, which are intermixed with Hcrt ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
1,098
4
16

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,844 publications
(1,168 citation statements)
references
References 19 publications
30
1,098
4
16
Order By: Relevance
“…Pre-prohypocretin is cleaved by proteolytic processing into two smaller peptides, hypocretin-1/orexin A (33 amino acids) and hypocretin-2/orexin B (28 amino acids). The distribution of hypocretin-containing neurons has been made in the mouse (Sakurai et al 1998;Wagner et al 2000), rat (De Lecea et al 1998;Peyron et al 1998;Nambu et al 1999), cat (Wagner et al 2000) and humans (Peyron et al 2000;Thannickal et al 2000). Neurons containing hypocretin are found only in the lateral hypothalamus (LH) from where they innervate virtually the entire brain and spinal cord (De Lecea et al 1998;Peyron et al 1998;Sakurai et al 1998;Nambu et al 1999).…”
Section: Hypocretin Neurons and Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-prohypocretin is cleaved by proteolytic processing into two smaller peptides, hypocretin-1/orexin A (33 amino acids) and hypocretin-2/orexin B (28 amino acids). The distribution of hypocretin-containing neurons has been made in the mouse (Sakurai et al 1998;Wagner et al 2000), rat (De Lecea et al 1998;Peyron et al 1998;Nambu et al 1999), cat (Wagner et al 2000) and humans (Peyron et al 2000;Thannickal et al 2000). Neurons containing hypocretin are found only in the lateral hypothalamus (LH) from where they innervate virtually the entire brain and spinal cord (De Lecea et al 1998;Peyron et al 1998;Sakurai et al 1998;Nambu et al 1999).…”
Section: Hypocretin Neurons and Receptorsmentioning
confidence: 99%
“…This was then supported by the finding that mice with deletion of the hypocretin/orexin gene exhibit symptoms of narcolepsy (Chemelli et al 1999). Recently, it was discovered that narcoleptic patients have a loss of the hypocretin-containing neurons (Peyron et al 2000;Thannickal et al 2000) and low CSF concentrations of HCRT-1 .…”
Section: Hypocretins and Narcolepsymentioning
confidence: 99%
“…Orexin (also known as hypocretin) is a neuropeptide that has been reported to play a role in the regulation of feeding, drinking, body temperature, general activity (Lubkin and Stricker-Krongrad, 1998;Edwards et al, 1999;Hagan et al, 1999;Kunii et al, 1999;Mondal et al, 1999;Piper et al, 2000;Estabrooke et al, 2001;Hungs et al, 2001;Yoshimichi et al, 2001;Kotz et al, 2002;Berthoud et al, 2005), energy homeostasis (Mintz et al, 2001), stimulation of gastric secretion in rats (Takahashi et al, 1999), increasing metabolic rate in rats (Lubkin and Stricker-Krongard, 1998), altering luteinising hormone release in rats (Pu et al, 1998) and in the regulation of the sleepwake cycle specifically associated with increased wakefulness and inhibition of REM sleep (Sakurai et al, 1998;Chemelli et al, 1999;Siegel, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Thannickal et al, 2000;van den Pol, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated dense projections to all monoaminergic cell groups and wake-promoting effects of hypocretins when administered centrally (Hagan et al 1999). More recently, clinical studies have shown that most patients with narcolepsy have undetectable hypocretins in the CSF and a striking decrease in hypocretin immunoreactivity and transcript levels in the perifornical hypothalamus Thannickal et al 2000). The most fre- quent cause of human narcolepsy is now known to be hypocretin deficiency, most probably as the result of an autoimmune attack against hypocretin-containing cells.…”
mentioning
confidence: 99%